0
$\begingroup$

I have another problem. Let $f(x) = e^{-a|x|}$ for $a>0$. Let $\widehat{f}(t) = \int_{\mathbb{R}} f(x) e^{-itx} dx = \dfrac{2a}{a^2+t^2} $ its Fourier transform.

I have to show that $\dfrac{a}{\pi(a^2+x^2)} * \dfrac{b}{\pi(b^2+x^2)} = \dfrac{a+b}{\pi((a+b)^2+x^2)}$, $b>0$.

With the convolution, I wrote $f_a(t) = \dfrac{a}{\pi(a^2+t^2)}$ when $t \in \mathbb{R}$ and $f_b(x-t) = \dfrac{b}{\pi(b^2+(x-t)^2)}$

The convolution is $f_a*f_b(x) = \int_{\mathbb{R}} f_a(t) f_b(x-t) dt$. We can compute this with a very long and tedious integration, and find the wished result. But is there any way to compute this with the Fourier transform ?

$\endgroup$
1
$\begingroup$

Indeed there is a way, denoting: $$\phi_a(x)=e^{-a|x|}$$ we have using your notations: $$\widehat{\phi_a}=f_a$$ But one of the properties of the Fourier transform is that: $$\widehat{f \times g}=f * g$$ So: $$\widehat{\phi_a \phi_b}=\widehat{\phi_a} *\widehat{\phi_b}=f_a * f_b$$

all it remains is to compute $\widehat{\phi_a \phi_b}$.

But as $e^{-a|x|} e^{-b|x|}=e^{-(a+b) x}$ you have: $$\phi_a \times \phi_b=\phi_{a+b}$$ thus: $$\widehat{\phi_a \phi_b}=\widehat{\phi_{a+b}}=f_{a+b}$$ and finally: $$f_a * f_b=f_{a+b}$$

$\endgroup$
1
$\begingroup$

Use the important relationship between convolution and Fourier transform.

$$f_a * f_b = \mathcal{F}^{-1}(\mathcal{F}(f_a) \cdot \mathcal{F}(f_b)).$$

Assuming the Fourier inversion theorem holds for these functions, all the necessary ingredients are already in your post.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.